A single bead - Engelman, Stephanie (Boston, MA : Pauline Books & Media, 2016)
A year after her grandmother's death in an airplane crash, Katelyn and her family visit the field where it happened, and Kate finds a single bead from her grandmother's rosary, and as more beads show up, Kate learns that people are crediting the beads with saving their lives--but can the story of the miraculous beads can save Kate's mother from the depression that is ruining her life?
Keywords: Rosary -- Juvenile fiction; Beads -- Religious aspects -- Catholic Church -- Juvenile fiction; Bereavement -- Juvenile fiction; Grief -- Juvenile fiction; Families -- Juvenile fiction; Depression, Mental -- Juvenile fiction; Rosary -- Fiction; Beads -- Religious aspects -- Fiction; Grief -- Fiction; Family life -- Fiction; Depression, Mental -- Fiction; Catholics -- Fiction; Christian life -- Fiction